Nanostructured Materials by High-Pressure Severe Plastic Deformation - Zhu, Yuntian T.; Varyukhin, Viktor; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Recently, it was reported that nanostructured materials processed under high pressure by HPT and ECAP have an extraordinary combination of both high strength and high ductility, which are two desirable, but rarely co-existing properties. These findings indicate that high-pressure is a critical factor that can be employed to process nanostructured materials with superior mechanical, and possibly also physical, properties. It is the objective of this workshop to review our current knowledge, identify issues for future research, and discuss future directions on the processing and properties of nanostructured materials via SPD techniques, with a special emphasis on high-pressure effects. The 42 peer-reviewed papers in this book cover areas of high pressure effect on the nanostructure and properties of SPD-processed materials, fundamentals of nanostructured materials, development of high-pressure SPD technologies for commercializations, recent advances of SPD technologies as well as applications and future markets of SPD-processed nanostructured materials.
Deformation Twinning in Nanocrystalline fcc Copper and Aluminum -- High Pressure in Large Plastic Deformation: Effects and Techniques -- Towards Comparison of Alternative Methods for Producing Bulk Nanostructured Metals by Severe Plastic Deformation -- Applications of Severe Plastic Deformations for Materials Nanostructuring Aimed at Advanced Properties -- New Applications of the SPD Concept: ?SPD -- Mechanisms of Submicron Grain Formation in Titanium and Two-Phase Titanium Alloy during Large Strain Warm Working -- Nanostructured and Polycrystalline Ti Anomalies of Low Temperature Plasticity -- Modeling of Grain Subdivision during Severe Plastic Deformation by VPSC Method Combined with Disclination Analysis -- Ultimate Grain Refinement by ECAP: Experiment and Theory -- Twist Extrusion as a Tool for Grain Refinement in Al-Mg-Sc-Zr Alloys -- Microstructural Characteristics of Ultrafine-Grained Nickel -- Refinement and Densification of Aluminum Nickelides by Severe Plastic Deformation -- Low-Temperature Sheet Rolling of TiAl Based Alloys -- Application of Diamond Anvil Cell Techniques for Studying Nanostructure Formation in Bulk Materials Directly during Severe Plastic Deformation -- Anomalous Nitrogen Solubility in Gradient Nanostructured Layer Formed in the Surface of Bulk Iron by Severe Plastic Deformation under Friction -- Evolution of Microstructure and Mechanical Properties of Ti-5Mo-5Al-5V Alloy Processed by High Pressure Deformation -- Martensitic Transformations in Nanocrystalline Fe-Cr-Ni and Fe-Mn Alloys -- Precipitation Behavior in Age-Hardenable Alloys after Severe Plastic Deformation -- Understanding the Textural and Microstructural Development in Two-Pass ECAP by Route A of a Commercial Aluminium Alloy -- Microstructural Refinement Of Bulk Nb And Ta by Severe Plastic Deformation for Composite Superconductor Applications -- Modeling Hardening Effects and Grain Size Evolution in Metals Induced by Severe Plastic Deformation -- Nanocrystalline Structure Formation under Severe Plastic Deformation and its Influence on Mechanical Properties -- Structure and Properties of Ti Alloys Processed by ECAP -- Microstructure and Mechanical Properties of 6082 Aluminum Alloy Processed by Hydrostatic Extrusion -- Grain Refinement and Viscous Fracture of Metals during Severe Plastic Deformation: Mathematical Simulation -- Structure and Properties of Ultrafine Grained Nickel after Severe Plastic Deformation -- Deformation Mechanisms Inducing Microstructure Refinement in Commercially Pure Aluminium Processed via ECAP: Comparison to Cold-Rolling and Hot-Torsion -- The Deformation Characteristics of Pure Aluminum Processed by Equal-Channel Angular Pressing -- Microstructural Aspects of Cyclic Deformation and Fatigue of Ultrafine-Grained Metals -- Modelling Mechanical Properties of SPD Materials During and After Severe Plastic Deformation -- Unique Deformation Behaviors of the Ultrafine Grained Aluminum Alloys Fabricated by Accumulative Roll Bonding -- Microstructure and Mechanical Properties of Long, Ultrafine-Grained Ti Rods -- Improving the Mechanical Properties of Ti-6Al-4V Alloy by Equal Channel Angular Pressing -- Structural Features, Strength, and Mechanisms of Deformation of Nanocrystalline Materials -- Response of Mechanical Properties across the Sample to ECAP -- Deformation and Failure of Ti-6Al-4V Nanostructured Alloy at 300-4.2 K -- Improvement of Mechanical Properties in a Nanostructured Fe-Ni-Mn Steel Prepared by Heavy Plastic Deformation -- Surface nanostructure and tribological properties of metallic materials -- Elevated Temperature Deformation Characteristics of Nanocrystalline Materials -- Features of Creep in Bulk Nanostructured Composite Cu-0.5wt.%Al2O3 -- Effect of Second Phase Particles on Annealing Ultrafine Grained Aluminium Alloys Deformed by ECAE -- The Influence of the SPD Regimes on Superplastic Behavior of an Aluminum Alloy.
Keywords: CHEMISTRY; MATERIALS; NANOTECHNOLOGY; CHEMISTRY; MATERIALS SCIENCE; NANOTECHNOLOGY; METALLIC MATERIALS; CONTINUUM MECHANICS AND MECHANICS OF MATERIALS